2015
DOI: 10.1097/fbp.0000000000000117
|View full text |Cite
|
Sign up to set email alerts
|

Tapentadol and nitric oxide synthase systems

Abstract: Tapentadol, a new analgesic drug with a dual mechanism of action (μ-opioid receptor agonism and norepinephrine reuptake inhibition), is indicated for the treatment of moderate to severe acute and chronic pain. In this paper, the possible additional involvement of the nitric oxide synthase (NOS) system in the antinociceptive activity of tapentadol was investigated using an unspecific inhibitor of NOS, L-NOArg, a relatively specific inhibitor of neuronal NOS, 7-NI, a relatively selective inhibitor of inducible N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
2
3
0
Order By: Relevance
“…The present study demonstrated that tapentadol produces antinociception in both phases of the orofacial formalin test. This study agrees with previous reports showing that tapentadol produces antinociception when administered systemically in animal models Christoph et al, 2011;Bujalska-Zadro_ zny et al, 2015;Ono et al, 2014] including the orofacial formalin test [Lee et al, 2015]. Furthermore, in the present study a dose-related antinociceptive effect of ketorolac was observed in both phases of the orofacial formalin in agreement with previous observations [Miranda et al, 1993;L opez-Muñoz et al, 2004;Isiordia et al, 2010].…”
Section: Discussionsupporting
confidence: 94%
“…The present study demonstrated that tapentadol produces antinociception in both phases of the orofacial formalin test. This study agrees with previous reports showing that tapentadol produces antinociception when administered systemically in animal models Christoph et al, 2011;Bujalska-Zadro_ zny et al, 2015;Ono et al, 2014] including the orofacial formalin test [Lee et al, 2015]. Furthermore, in the present study a dose-related antinociceptive effect of ketorolac was observed in both phases of the orofacial formalin in agreement with previous observations [Miranda et al, 1993;L opez-Muñoz et al, 2004;Isiordia et al, 2010].…”
Section: Discussionsupporting
confidence: 94%
“…The present study shows that the systemic administration of tapentadol produces a dose‐dependent antinociceptive effect in a mouse model of visceral pain in agreement with other reports (Bujalska‐Zadrożny, Wolińska, Gąsińska, & Nagraba, ; Christoph, De Vry, Schiene, Tallarida, & Tzschentke, ; Ono et al, ; Schiene, De Vry, & Tzschentke, ) that included the acetic acid‐induced writhing test (Zapata‐Morales et al, ). Likewise, systemic diclofenac showed a dose‐dependent antinociceptive action in the acetic acid‐induced visceral pain assay in mice again in agreement with other reports (León‐Reyes, Castañeda‐Hernández, & Ortiz, ; Ortiz, ; Ortiz et al, ), that included the writhing test (Goh et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, it is possible that other mechanisms of antinociceptive action are involved in the activity of this drug. Recently, a study demonstrated the involvement the L‐arginine–NO–cGMP system in the tapentadol antinoception in Randall‐Selitto and tail‐flick tests [Bujalska‐Zadrożny et al, ]. Similarly, the action of ketorolac is mainly through cyclooxygenase inhibition, it may also activate endogenous opioid system via descending pathways in the spinal cord and brain [Uphouse et al, ; Tripathi and Welch, ].…”
Section: Discussionmentioning
confidence: 99%